Robust nonnegative matrix factorization with local coordinate constraint for image clustering. (February 2020) - Peng, Siyuan; Ser, Wee; Chen, Badong; Sun, Lei; Lin, Zhiping
Abstract: Nonnegative matrix factorization (NMF) has attracted increasing attention in data mining and machine learning. However, existing NMF methods have some limitations. For example, some NMF methods seriously suffer from noisy data contaminated by outliers, or fail to preserve the geometric information of the data and guarantee the sparse parts-based representation. To overcome these issues, in this paper, a robust and sparse NMF method, called correntropy based dual graph regularized nonnegative matrix factorization with local coordinate constraint (LCDNMF) is proposed. Specifically, LCDNMF incorporates the geometrical information of both the data manifold and the feature manifold, and the local coordinate constraint into the correntropy based objective function. The half-quadratic optimization technique is utilized to solve the nonconvex optimization problem of LCDNMF, and the multiplicative update rules are obtained. Furthermore, some properties of LCDNMF including the convergence, relation with gradient descent method, robustness, and computational complexity are analyzed. Experiments of clustering demonstrate the effectiveness and robustness of the proposed LCDNMF method in comparison to several state-of-the-art methods on six real world image datasets. Highlights: The LCDNMF algorithm is proposed. The convergence and relation with gradient descent method of LCDNMF is analyzed. The robustness and computational complexity of LCDNMF is also analyzed. Experiment results show the effectiveness and robustness of LCDNMF.